The Level Of Physical Fitness On The Athletes Achievements Of The FIKK UNM Athletic Club (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
Physical fitness is a fundamental factor that supports athlete performance and achievement in sports, particularly in athletics, which requires optimal endurance, strength, speed, and agility. Athletes with good physical fitness are generally able to perform movements more efficiently, maintain performance during competition, and reduce the risk of fatigue. Therefore, evaluating the level of physical fitness and its relationship with athlete performance is important in order to understand the factors that contribute to athletic success. This study aimed to examine the relationship between physical fitness levels and athlete achievements among members of the FIKK UNM Athletic Club.This research employed a quantitative approach with a correlational research design. The sample consisted of 20 athletes selected using a purposive sampling technique. Physical fitness data were collected through standardized fitness tests measuring endurance, arm muscle strength, and agility. Meanwhile, athlete achievement data were obtained from official records of recent competitions participated in by the athletes. Data analysis was conducted using the Pearson Product Moment correlation test to determine the relationship between physical fitness components and athlete performance, while multiple linear regression analysis was used to examine the simultaneous contribution of the physical fitness variables. The results revealed a significant positive relationship between physical fitness components and athlete achievements. Endurance showed a correlation value of r = 0.67 (p = 0.000), arm muscle strength r = 0.55 (p = 0.000), and agility r = 0.51 (p = 0.001). Furthermore, regression analysis indicated that endurance, arm muscle strength, and agility simultaneously contributed 77% to athlete performance. In conclusion, physical fitness plays an important role in determining the achievements of athletes in the FIKK UNM Athletic Club. Improving endurance, muscular strength, and agility through systematic training programs can significantly enhance athlete performance in athletics competitions.